If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3s + -18 = 24 + 9s Reorder the terms: -18 + 3s = 24 + 9s Solving -18 + 3s = 24 + 9s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-9s' to each side of the equation. -18 + 3s + -9s = 24 + 9s + -9s Combine like terms: 3s + -9s = -6s -18 + -6s = 24 + 9s + -9s Combine like terms: 9s + -9s = 0 -18 + -6s = 24 + 0 -18 + -6s = 24 Add '18' to each side of the equation. -18 + 18 + -6s = 24 + 18 Combine like terms: -18 + 18 = 0 0 + -6s = 24 + 18 -6s = 24 + 18 Combine like terms: 24 + 18 = 42 -6s = 42 Divide each side by '-6'. s = -7 Simplifying s = -7
| 2r-25=-34+3r | | 7x^4+62x^2-9=0 | | 3y-7=-3y+-9 | | 81x^2+484=8 | | 4(x+3)=7x+15 | | X+7.5=-8 | | 7(3n+7(n+k)+2k)= | | V*2=80 | | 5+5b=2.5b | | y=(c-k)x+1 | | X+7.5=8 | | x^4+2x^2-80=0 | | 6(P+24)=414 | | -2z+4=-27.2+2z | | c=clt | | c=cult | | c=cly | | 5logx=8 | | -81=b-3(7-3b) | | 22=(x-300000)/x | | 7x=-45 | | k=8r-s | | 0.45(6)+0.05x=0.15(12+x) | | 2z+1.1=0+3z | | 120=x+(x-3) | | 10-(2y-4)=7-3y | | 2x^2-242= | | 3m^4+18m^2-120=0 | | 3v+30=-3(v+2) | | 4x^2+20x+106=0 | | (4y^2-5y^3)-(6y^2+5y+7)= | | 2z^2-z-1=0 |